Nonstationary Fronts in the Singularly Perturbed Power-Society Model - M. G. Dmitriev; A. A. Pavlov; A. P. Petrov (Abstract and Applied Analysis)
The theory of contrasting structures in singularly perturbed boundary problems for nonlinear parabolic partial differential equations is applied to the research of formation of steady state distributions of power within the nonlinear “power-society” model. The interpretations of the solutions to the equation are presented in terms of applied model. The possibility theorem for the problem of getting the solution having some preassigned properties by means of parametric control is proved.